2016
DOI: 10.1161/circep.115.003461
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly High Incidence of Stroke and Left Atrial Appendage Thrombus Formation After Electrical Isolation of the Left Atrial Appendage for the Treatment of Atrial Tachyarrhythmias

Abstract: After LAAI, an unexpectedly high incidence of LAA thrombus formation and stroke was observed despite OAC therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(138 citation statements)
references
References 21 publications
4
129
3
2
Order By: Relevance
“…Second, regarding the technique of LAAI in our study population, 2 we fully agree with Briceno et al that a wide-area LAAI is different from the LAAI technique described by Di Biase et al, 3,4 which is more or less restricted to local ablation close to the base of the LAA and may have a lower chance of persistent isolation of the LAA. The risk of LAA thrombus formation using this technique might be lower, as was shown in the recently presented data from the BELIEF trial.…”
Section: In Responsesupporting
confidence: 86%
“…Second, regarding the technique of LAAI in our study population, 2 we fully agree with Briceno et al that a wide-area LAAI is different from the LAAI technique described by Di Biase et al, 3,4 which is more or less restricted to local ablation close to the base of the LAA and may have a lower chance of persistent isolation of the LAA. The risk of LAA thrombus formation using this technique might be lower, as was shown in the recently presented data from the BELIEF trial.…”
Section: In Responsesupporting
confidence: 86%
“…There are ethical concerns about the extensive ablation strategy used by Rillig et al, 7 particularly in patients with paroxysmal AF (40% of patients who underwent LAA isolation). After pulmonary vein isolation, the majority of patients with LAA isolation received a mitral isthmus line (94%) and an anterior line (90%).…”
Section: See Article By Rillig Et Almentioning
confidence: 99%
“…More work is required to delineate the risks, benefits, and hemodynamic impact of LAA isolation, and the methods to achieve this. We must thank Rillig et al 7 for reporting what had been a more theoretical risk with electric LAA isolation, and their work should serve as an important guide and resource to the reader.…”
Section: See Article By Rillig Et Almentioning
confidence: 99%
“…In contrast, Rillig et al found that 21% of patients developed an LAA thrombus after LAA ablation despite 90% of patients receiving oral anticoagulation at the time. However, LAA ablation in this study included electrical isolation of the LAA base using bidirectional block of both an anterior and mitral isthmus line, which may explain the increased stroke risk 42. On the other hand, all studies included in this meta‐analysis made use of distal LAA isolation.…”
Section: Discussionmentioning
confidence: 99%